Modelling and ride analysis of a hydraulic interconnected suspension based on the hydraulic energy regenerative shock absorbers. (15th July 2019) - Zou, Junyi; Guo, Xuexun; Abdelkareem, Mohamed A.A.; Xu, Lin; Zhang, Jie
Graphical abstract: Highlights: A novel design of a HIS-HESA based on a 7-DOF full vehicle model was presented. Different HIS-HESA working modes including bounce, pitch and roll modes were investigated. HIS-HESA can harvest a maximum power of 397 W at 72 km/h and class C ISO-road. The ride comfort and road holding using the HIS-HESA were improved by 33% and 20%. Controlling the external resistance can realize the trade-off between ride comfort and energy recovery. Abstract: The suspension system is an important part which can mitigate the influences of vibration caused by road roughness where these vibrations are traditionally dissipated by shock absorbers. From the view of energy recovery, a hydraulic interconnected suspension based on the energy regenerative shock absorbers (HIS-HESA) is proposed to improve ride comfort, road holding ability and energy recovery ability simultaneously. This paper mainly focuses on the modelling and ride analysis of a 7-DOF full vehicle suspension model integrated with the HIS-HESA. The mathematical model of the HIS-HESA is described based on the relationship between the pressure drop and the flow rate of every hydraulic element. The characterization of the HIS-HESA is given based on a parametrical analysis under a sinusoidal excitation. Further, the traditional shock absorber and the single HESA have been compared terms of suspension dynamics and energy recovery. Thereafter, the simulation is implemented to compare the vehicle dynamics (body acceleration, tire dynamic load and power regenerated) using HIS-HESA with that of the traditional suspension. The simulation results suggest that the HIS-HESA can attenuate the vibrations to maintain a good ride comfort besides it can also regenerate energy to power electrical equipment on the vehicle. The analysis also indicates that the influence of external resistance within HIS-HESA provides the possibility regarding the semi-active control of the HIS-HESA which will be the research focus in future development.